Translating Heaney: a study of Sweeney astray, The cure at Troy, and Beowulf - Van der Woude, Peter William (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2007)
This thesis examines Seamus Heaney's approach to translation with specific reference to Sweeney Astray, The Cure at Troy, and Beowulf. An assessment of Heaney's translations, and the ways in which they relate to his poetry, is essential to an understanding of his work as a poet. This thesis demonstrates the centrality of translation to Heaney's oeuvre as an effective means to comment on his Northern Irish socio-political context without producing political propaganda. Translation is a valuable means for Heaney to elucidate his contemporary experience by considering it in terms of the recorded past captured within his chosen translations. Instead of comparing the three translations with their original texts, this thesis concentrates on Heaney's translations as a continuation of his own creative work and as catalysts for further poetry. The translations are explored in chronological order to allow a sense of Heaney's development as a translator and his efforts to remain critically attuned to the Northern Irish political situation. The first chapter examines Heaney's translation of the Gaelic poem Buile Suibhne, which is published as Sweeney Astray. In this first major act of translation Heaney recognises the political role that translation is able to play. He draws attention to the protagonist's sense of cultural ease in both Britain and Ireland, which he argues is exemplary for the people of Ulster and renders the narrative particularly accessible to a Northern Irish readership due to his anglicisation of the text, which is intended as a reminder to both Catholics and Protestants of their shared identity as Irishmen. The second chapter focuses on Heaney's translation of Sophocles' Philoctetes, entitled The Cure at Troy. Heaney's translation contextualises the Ancient Greek concern for personal integrity in the face of political necessity, a situation relevant to his own complex relationship with Northern Irish politics. His alterations to the text accentuate the positive aspects of the play, suggesting the very real possibility of social change within the seemingly constant violence of Northern Ireland. The third chapter explores Heaney's engagement with the Anglo-Saxon epic poem, Beowulf, as a means of coming to terms with the complex history of Irish colonisation through language. This chapter assesses Heaney's incorporation of Irish dialectal words into his translation, which lend the poem political weight, and yet prove to be contextually appropriate, rendering Heaney's Beowulf a masterpiece of readability and subtle political commentary.
Keywords: Heaney, Seamus, 1939- -- Criticism and interpretation; Heaney, Seamus, 1939- -- Sweeney astray; Sophocles -- Philoctetes -- Translations -- History and criticism; Beowulf -- Translations -- History and criticism; Buile Suibhne Geilt; Buile Suibhne Geilt -- Translations -- History and criticism